Порівняльний аналіз сценаріїв розгортання інфраструктури у хмарному середовищі - Красюкова, В. В. (ХНУРЕ, 2024)
The process of deploying infrastructure in a cloud environment is one of the key stages that ensures the efficiency of using this infrastructure in the future. The physical location and ownership structure of the cloud environment play a significant role in the effectiveness of cloud computing applications. According to their combination, four deployment scenarios are distinguished. To choose a scenario, it is necessary to analyze the advantages and disadvantages of each of them, as well as evaluate one's own needs, requirements, and capabilities.
Keywords: хмарне середовище; сценарії розгортання інфраструктури у хмарному середовищі